Rheology and Pipeline Flow Behavior of Fumed Silica Nanoparticle Suspensions - Singh, Arshdeep (University of Waterloo, 2018)
Suspensions are used in a wide variety of industrial and household applications; some examples being paints, ink, wastewater streams, cough syrups, and sauces. Rheology of suspensions depends on various factors such as the particle size, shape and their surface chemistry other than the nature of the continuous phase. Nanoparticles, when used to produce suspensions offer unique rheological properties due to their extremely small size and high surface area. In this study, fumed silica nanoparticles of hydrophilic grade were used to form suspensions in water. Three different hydrophilic grades of fumed silica nanoparticles were chosen for rheological studies. Various properties such as zeta potential, particle size distribution, rheological and pipeline flow behavior were studied as a function of concentration, pH change, temperature, and presence of an electrolyte in the study. The results show that the silica nanoparticles form stable suspensions in water. The suspensions show shear-thinning behavior for the range of shear rates investigated. With an increase in particle concentration, the suspensions become more and more viscous. The Dynamic light scattering results show that the particle size increases with an increase in concentration. The shear viscosity decreases with an increase in temperature. Zeta potential results show that the particles are negatively charged in the aqueous phase and zeta potential value decreases in magnitude with an increase in particle concentration. The size distribution peaks do not show any pattern with a change in pH in the absence of an electrolyte whereas, in the presence of an electrolyte, the peaks move toward higher particle size confirming the presence of bigger aggregates in the presence of an electrolyte. The relative viscosity of suspensions increases more rapidly than the Einstein equation for hard spheres. Also, the relative viscosity at low pH value is higher for very low particle concentration suspensions but with an increase in concentration, suspensions show higher viscosity at high pH values. An addition of an electrolyte has a sharp increasing effect on the viscosity of dilute suspensions. Also, zeta potential turns more and more negative with increase in pH in the absence of an electrolyte whereas zeta potential values get compressed in the presence of an electrolyte. Pipeline flow results show that suspensions show drag reduction characteristics for very low particle concentration samples whereas almost no drag reduction properties for relatively higher particle concentration suspensions.